2014
DOI: 10.1186/s12955-014-0131-2
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cross-sectional study on quality of life and treatment satisfaction in type 2 diabetic patients with retinopathy without other major late diabetic complications

Abstract: Background: To assess quality of life and treatment satisfaction in patients with type 2 diabetes mellitus with diabetic retinopathy (DR) using validated instruments, with comparison to patients without DR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
68
1
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(93 citation statements)
references
References 31 publications
(42 reference statements)
18
68
1
6
Order By: Relevance
“…In our study, glycemic control was not associated with HRQoL while patients with complications showed lower QoL scores than patients without complications, though this difference was not statistically significant. Additionally, men with T2DM reported higher scores in present QoL than women, a finding consistent with other studies in similar populations (9,12,(26)(27)(28)(29). Several studies showed that the most negatively impacted domains were those related to food, namely, 'freedom to eat', 'enjoyment of food' and 'freedom to drink'.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, glycemic control was not associated with HRQoL while patients with complications showed lower QoL scores than patients without complications, though this difference was not statistically significant. Additionally, men with T2DM reported higher scores in present QoL than women, a finding consistent with other studies in similar populations (9,12,(26)(27)(28)(29). Several studies showed that the most negatively impacted domains were those related to food, namely, 'freedom to eat', 'enjoyment of food' and 'freedom to drink'.…”
Section: Discussionsupporting
confidence: 88%
“…Most participants were women (52.4%), which contradict the higher prevalence of diabetes in men observed in Portugal [8]. This situation was also described and analyzed by Morais and colleagues (2015), who concluded that this may be, to some extent, associated with gender-related cultural issues, i.e.…”
Section: Discussionmentioning
confidence: 76%
“…As a chronic disease, diabetes can lead to long-term microvascular and macrovascular complications [4][5][6]. It has a negative impact on individuals, affecting all spheres of life and reducing their quality of life [7,8]. The psychosocial [9] and psychological [10,11] problems associated with diabetes, as well as the burden of disease and the lifestyle restrictions of diabetic patients are widely addressed in the literature [12].…”
Section: Introductionmentioning
confidence: 99%
“…These differences may also be influenced by the type of tools used, as well as different cultural and social structure. According to the results, the quality of life in patients with non-proliferative retinopathy was better than patients with proliferative retinopathy; the study results of Alcubierre et al in Germany showed that the severity and degree of retinopathy have a negative effect on patients' quality of life [27]. Accordingly, as proliferative retinopathy has more severe symptoms, it can affect individuals' abilities and quality of life more than the no proliferative type.…”
Section: Discussionmentioning
confidence: 96%